DEVELOPMENT OF GEOMETRICAL TEST MODULE OF MILLING MACHINE BASED ON ISO STANDARD WITH CASE STUDY CNC MACHINE VMC 250 - NORIZKI (NIM : 13104056); Pembimbing 1 : Prof. Dr. Ir. Yatna Yuwana M.; Pembimbing 2 : Dr., JULFIKAR
A milling machine is a machine tool used to machine materials with prismatic shape. Milling machine can perform a vast number of cutting operations, such as gears production, groove making, planing, drilling, diesinking, facing, etc. Because they are capable of performing a variety of cutting operations, milling machines are among the most crucial and versatile machine tools. Final dimension of a product that can be made by milling process is expected to have a qualified accuracy which is requested thus stated at its geometric tolerances (dimension, shape, position, and surface roughness). Therefore, a systematic and complete testing procedure to check the accuracy of milling machine is needed. Nine testing methods for milling machines were obtained from ISO 1984 (Test conditions for milling machines with table of fixed height with vertical spindle). To check the procedures that had been made, a case study at CNC Machine VMC 250 had to be done. Finally, the first conclusion could be obtained by knowing whether the module that has been made could fulfill the standard and could be applied when testing the CNC Machine VMC 250. Then, the second conclusion to know the geometric accuracy of CNC Machine VMC 250 could be obtained through comparing the deviation which is acquired through testing, with the geometric tolerance that is stated by ISO 1984. At last, it is expected from the suggestions given at this final project, could be applied and could improve this geometrical test module of milling machine.